2012
DOI: 10.1007/s10878-012-9513-8
|View full text |Cite
|
Sign up to set email alerts
|

The game Grundy number of graphs

Abstract: Given a graph G = (V, E), two players, Alice and Bob, alternate their turns in choosing uncoloured vertices to be coloured. Whenever an uncoloured vertex is chosen, it is coloured by the least positive integer not used by any of its coloured neighbours. Alice's goal is to minimize the total number of colours used in the game, and Bob's goal is to maximize it. The game Grundy number of G is the number of colours used in the game when both players use optimal strategies. It is proved in this paper that the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In order to tighten specific bounds for the game-chromatic number it may be necessary to design winning strategies for Alice that are not 'colourblind'. A further 'first-fit' variant of the graph colouring game is the Grundy colouring game introduced by Havet and Zhu (2013). The game-chromatic number has also been studied in the context of random graphs (Bohman et al, 2008).…”
Section: Motivationmentioning
confidence: 99%
“…In order to tighten specific bounds for the game-chromatic number it may be necessary to design winning strategies for Alice that are not 'colourblind'. A further 'first-fit' variant of the graph colouring game is the Grundy colouring game introduced by Havet and Zhu (2013). The game-chromatic number has also been studied in the context of random graphs (Bohman et al, 2008).…”
Section: Motivationmentioning
confidence: 99%
“…Finally, we address a question raised by Havet and Zhu [7,Problem 4] whether there is a function f such that all graphs G satisfy χ g (G) f (Γ g (G)). The following and the fact that Γ g (G) Γ (G) imply that the answer is no.…”
Section: Conjecturementioning
confidence: 99%
“…The Grundy game was introduced recently by Havet and Zhu [7], who showed that Γ g (F ) = 3 and Γ g (Q) 7. To our knowledge, the asymmetric Grundy games were not considered yet.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Havet and Zhu [9] proposed the greedy coloring game and the game Grundy number Γ g (G). They proved that Γ g (G) ≤ 3 in forests and Γ g (G) ≤ 7 in partial 2-trees.…”
Section: Introductionmentioning
confidence: 99%
“…They also posed two questions. Problem 5 of [9]: χ g (G) can be bounded by a function of Γ g (G)? Problem 6 of [9]: Is it true that Γ g (G) ≤ χ g (G) for every graph G?…”
Section: Introductionmentioning
confidence: 99%